2021
DOI: 10.1021/acssuschemeng.1c07104
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Thermostability of Engineered Laccases in Aqueous Betaine-Based Natural Deep Eutectic Solvents

Abstract: In recent years, natural deep eutectic solvents (NADESs) have gained increasing attention as promising nontoxic solvents for biotechnological applications, due to their compatibility with enzymes and ability to enhance their activity. Betaine-based NADESs at a concentration of 25 wt % in a buffered aqueous solution were used as media to inhibit thermal inactivation of POXA1b laccase and its five variants when incubated at 70 and 90 °C. All the tested laccases showed higher residual activity when incubated in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 47 publications
2
20
1
Order By: Relevance
“…It is well-known that the properties of DESs are governed by their compositions, which affect their compatibility with enzymes, influencing the activity and thermostability of the enzymes. Fortunately, numerous studies on the performance of enzymes in a variety of DESs have been reported by research groups. ,,, To further elucidate the impacts of DESs on the thermostability of FA-HY1, the thermostability of FA-HY1 was observed with betaine/glycerol and ChCl/sorbitol under a variety of water conditions. As detailed in Figure a,b, FA-HY1 exhibited comparable stability in the presence of DESs with different water activity at 40 °C, and more than 80% of initial enzyme activity in the NaPb was retained after 24 h (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-known that the properties of DESs are governed by their compositions, which affect their compatibility with enzymes, influencing the activity and thermostability of the enzymes. Fortunately, numerous studies on the performance of enzymes in a variety of DESs have been reported by research groups. ,,, To further elucidate the impacts of DESs on the thermostability of FA-HY1, the thermostability of FA-HY1 was observed with betaine/glycerol and ChCl/sorbitol under a variety of water conditions. As detailed in Figure a,b, FA-HY1 exhibited comparable stability in the presence of DESs with different water activity at 40 °C, and more than 80% of initial enzyme activity in the NaPb was retained after 24 h (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…These solvents have an effect on the enzymes, modifying properties such as stability and activity. , However, a majority of these solvents are hazardous materials and generally damage the enzymes. Therefore, significant efforts have been made to find other promising sustainable solvents to achieve the requirement of being environmentally friendly. To this aim, deep eutectic solvents (DESs) have been synthesized through the combination of hydrogen-bonding acceptors (HBAs) and hydrogen-bonding donors (HBDs) derived from biobased constituents, including choline derivatives, betaine, alcohols, amino acids, and sugars. Due to their attractive physicochemical properties such as low melting point, low vapor pressure, and environmental friendliness, The use of DESs as sustainable solvents for the application of several categories of enzymes in biocatalysis has become widespread, including alcohol dehydrogenases, , horseradish peroxidases, laccases and lipases. , These published articles propose that the massive hydrogen-bonding networks in the DES systems result in milder conditions for the improvement of enzyme activity and thermostability . The addition of water into a pure DES system has been investigated to determine the impact on its inherent properties, including high viscosity, that hinder applications within engineering fields.…”
Section: Introductionmentioning
confidence: 99%
“…Besides their low flammability, low volatility, high thermal stability, facile preparation, reduced cost, and biodegradability, the main interest in NADESs originates from the wide scope of potential applications as cosolvent or reaction medium in a broad range of enzymatic reactions, resulting in higher product conversion and enhanced enantioselectivity [14,18]. Furthermore, incubation of enzymes in NADESs can be suggested as an alternative post-synthesis approach to avoid their thermal inactivation at high temperatures [19,20], which is typically observed in organic solvents [21].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] The molar ratio of HBA and HBD were correlated to the enzyme behaviors in DESs. [19][20][21] This conflicting information suggested that more detailed studies are highly required. Many techniques from different aspects can study the enzyme-DES interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The thermostability of laccase was related to the H‐bond interaction between the hydroxyl groups of HBD in DESs and the amino acids in laccase [19,20] . The molar ratio of HBA and HBD were correlated to the enzyme behaviors in DESs [19–21] . This conflicting information suggested that more detailed studies are highly required.…”
Section: Introductionmentioning
confidence: 99%